Behavioral Anomalies in Contingent Values and Actual Choices. (30th August 2016) - Poe, Gregory L.
Abstract : A growing body of literature demonstrates that many behavioral anomalies observed in stated-preference elicitation methods such as the contingent valuation method are also observed in actual choices and vice versa. This presentation furthers the argument that such parallel behaviors should be viewed as a strength of stated-preference methods. Three well-known anomalies observed in both stated preferences and actual choices are first reviewed to lay the foundation for this argument. A number of lesser-known anomalies are then presented to demonstrate the wider prevalence of parallel anomalies in stated preferences and actual choices.